Implementasi Materi Thaharah Dalam Membentuk Budaya Hidup Bersih Peserta Didik Di MTs Negeri 1 Maluku Tenggara Dan Mts Raudah Kota Tual - Linda; N, Rustina; Abd Rahman, Muhajir (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2024)
Learning Islamic Religious Education Thaharah material at the MTs level is a concern in the formation of a daily clean living culture. The purpose of this study was to determine the implementation of Thaharah material in shaping the clean living culture of students at MTs Negeri 1, for qualitative descriptive research penis. Data collection techniques interviews, observation and documentation. The research findings are: (1) Learning thaharah material at MTsN 1 Malra and MTs Raudah Tual City has similarities and runs well and effectively. Teachers in both schools use the lecture and practice methods in explaining thaharah material. The lecture method is used to explain the basic concepts of thaharah, while practice is used to ensure students can directly practice the procedures for purification such as ablution and ghusl correctly. Both methods proved effective in delivering the thaharah material to the students; (2) The thaharah material had a positive effect on the cleanliness culture of the students in both schools, as reflected in the cleanliness of the school environment and the students' personal hygiene. During the observation, it was found that the students had clean clothes, neat haircuts, and clean nails, indicating that students' awareness to maintain cleanliness is not only triggered by the existing rules, but also by the religious values that have been internalized in them. Cleanliness has become part of students' character and personal identity, reflecting the strong influence of the thaharah material taught at school. Thus, it can be concluded that the thaharah material not only succeeds in teaching students the correct way to purify themselves, but also plays an important role in fostering awareness of the importance of cleanliness.